PENGARUH PENERAPAN MEDIA AUGMENTED REALITY BERBASIS DISCOVERY LEARNING TERHADAP HASIL BELAJAR PADA MATERI DARAH - Purnamasari, Dian; Sudarisman, Suciati; Dwiastuti, Sri (BIO-PEDAGOGI, 2016)
The research was aimed to ascertain the influence of application augmented reality media based discovery learning toward learning achievement. The research was quasi experimental research, using post-test only with non-equivalent groups. The population was all students of XI IPA MAN 2 Surakarta in Academic Year 2014/2015, which is divided into 3 classes. The sampling technique used in the research was a cluster sampling. Sample was used class XI IPA 2 consist of 22 siswa for control class with image media with konvensional learning ang class XI IPA 1 consist of 22 siswa for experiment class with augmented reality media based discovery learning. The data were collected using tests and non-tests techniques. Tests techniques using tests method multiple choice and short essay to measure learning achievement in knowled domain, while non-test techniques observation method using observation sheet to measure learning achievement in skills domain and attitude domain. The hypothesis was analyzed with t-test and mann-whitney test using SPPS version 16. The result showed learning achievement knowledge domain (Sig. 0,000 < 0,05), skills domain (Sig. 0,003 < 0,05), and attitude domain (Sig. 0,008 < 0,05). Based on the result to indicate signification of learning achievement < 0,05 so there were difference effects of application augmented reality media based discovery learning with konvensional learning toward learning achievement.Â Keywords: augmented reality media, discovery learning, learning achievement.